Accrual accounting reform: a learning curve for Malaysia - Rosaidy Mahadi; Raman Noordin; Rasid Mail; Kaziemah Sariman (INSInet Publications, 2015)
Background: Public sector reform is now initiated more aggressively under various terms of reference, such as transparency, better governance, and delivery efficiency and effectiveness. For Malaysia it is clearly motivated by both internal and external pressure to face the challenges and harnessing the global trend of change. Under current financial policy, both income and expenditure are clearly stated as the critical area of concern. Therefore Malaysian government is targeting accrual system to be fully implemented in its public sector by 2016. Objective: This paper examines the problems faced by the entity entrusted to be responsible to implement the accrual accounting in the public sector. Results: The findings showed that the shift towards accrual accounting demonstrates some problems in implementation such as recognition and valuation of assets and liabilities, human competency and, systems and technological development. These implementation barriers are among the reasons why developing countries should be cautious in considering accrual accounting reform. Conclusion: The adoption to accrual accounting will be a long challenge and it needs support from everyone to make it as a success with the hope for Malaysia to be one of the developed countries by 2020